The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s11095-014-1586-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell Penetrating Peptides as Efficient Nanocarriers for Delivery of Antifungal Compound, Natamycin for the Treatment of Fungal Keratitis

Abstract: The formation of CPP-natamycin complex is clinically significant as it may enhance the bioavailability of natamycin in corneal tissues and aid in efficient management of fungal keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Here, we adopted a different strategy based on the use of CPPs as delivery vehicles. Many organic molecules, such as the anticancer drug doxorubicin (74) or the antifungal drug natamycin (75), have been successfully delivered by CPPs and their therapeutic efficacy has been increased. Recently, Abushahba et al (76) used CPPs to deliver peptide nucleic acids (PNAs) targeting bacterial genes, such as RNA polymerase, to kill Listeria monocytogenes in vitro, or in cell culture and in C. elegans infection models.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we adopted a different strategy based on the use of CPPs as delivery vehicles. Many organic molecules, such as the anticancer drug doxorubicin (74) or the antifungal drug natamycin (75), have been successfully delivered by CPPs and their therapeutic efficacy has been increased. Recently, Abushahba et al (76) used CPPs to deliver peptide nucleic acids (PNAs) targeting bacterial genes, such as RNA polymerase, to kill Listeria monocytogenes in vitro, or in cell culture and in C. elegans infection models.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of drug resistance, where pathogen membrane provides a significant barrier, intracellular delivery of antibiotics/drugs by the virtue of CPP, proved to be a vital step in combating drug resistance to some extent (Sparr et al, 2013 ). CPP based conjugates (Ganguly et al, 2008 ; Jain et al, 2015 ) and combination therapy has been explored against several resistant pathogens (Randhawa et al, 2016 ). They have been proved effective against intracellular pathogens too (Gomarasca et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although their mechanism of entry inside the cells remains highly debated, they are still used to deliver numerous pharmaceutical molecules inside various types of cells. In our previous study [10], we have successfully shown cellular uptake as well as enhanced antifungal activity of TAT 2 conjugated Natamycin in human corneal epithelial cell line. Now to further test the antifungal efficacy in vivo, we have developed a murine model of fungal keratitis using clinical isolate of Fusarium dimerum.…”
Section: Introductionmentioning
confidence: 87%